Utilization of Tofu By-Products as Cattle Feed within an Integrated Agribusiness Framework - Ambar , Abdul Azis; Rahmat, Rahmat; SL, Nurfadila; Liani, Putri (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Tofu waste is an agro-industrial by-product with significant potential as an alternative feed for cattle due to its relatively good nutritional content and abundant availability. This study aims to analyze the utilization of tofu waste as cattle feed from an integrated agribusiness perspective, covering upstream to downstream aspects. The research method employs a literature review and a qualitative descriptive approach by examining various scientific sources related to animal feed, the tofu agro-industry, and agribusiness systems. The results indicate that the utilization of tofu waste not only reduces feed costs but also supports the efficiency of livestock enterprises, minimizes environmental waste, and creates business linkages among agribusiness subsectors. Therefore, the utilization of tofu waste as cattle feed represents a strategic alternative for supporting the development of sustainable integrated agribusiness.